Percepção arquitetônica do espaço de trabalho pela comunidade universitária: estudo de caso da UFSCar - Campus São Carlos - Salvador, Elizabeth Valdetaro (Universidade Federal de São Carlos, 2011)
The main objective of this work was to search and to analyze the architectural perception of the community of UFSCar campus working space, composed by its teachers and administrativetechnician personnel, with the intention to subsidize the elaboration of future studies and projects of architecture in the University with a more effective participation of these users. Based on a bibliographical research and a theoretical reference developed, several attributes of the working space were defined for a qualitative and quantitative analysis of the users perception. To this purpose, a research with the university community was carried on the internet by the application of questionnaires on the related attributes, being previously associated to each one a scale of values. Besides the evaluation of the attributes of the working space, which is understood as where the users spend most of their time, the questionnaires also approached other aspects as sex, age, level of education, department/sector, time at the working place and at the University, with the objective of getting to know the respondents profile. Interviews had also been carried on the internet with architects who worked as directors and/or related to planning and project in the University sectors responsible for these activities, since 1976 until now. The answers of the questionnaires had been systemized, statistically treated and duly analyzed qualitatively and quantitatively. The architects answers were analyzed qualitatively. As the result of the research with the users, it was verified that their perception of the working space is diversified, similar in certain aspects and very divergent in others. The reason is that ambient conditions are also different depending on the work place and some people are in much better places than others. The youngest users and those who work in the Center of Human Sciences clearly tended to be more negative in their perception. The result of the interviews with the architects shows the importance of planning and project processes in an integrated and continuous way, so that the quality of the constructed space is guaranteed throughout the years, independent of circumstantial factors that can influence the expansion of the University in the short-term. It is essential to give an answer to the urgent problems without losing the perspective and objectives in long-term.
Keywords: Projeto arquitetônico; Percepção; Ambiente de trabalho; Usuários; Campus universitário; ENGENHARIAS